2010
DOI: 10.1093/sysbio/syp104
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Analysis of Lateral Gene Transfer in Thymidylate Synthase Enzymes

Abstract: Thymidylate synthases (Thy) are key enzymes in the synthesis of deoxythymidylate, 1 of the 4 building blocks of DNA. As such, they are essential for all DNA-based forms of life and therefore implicated in the hypothesized transition from RNA genomes to DNA genomes. Two evolutionally unrelated Thy enzymes, ThyA and ThyX, are known to catalyze the same biochemical reaction. Both enzymes are sporadically distributed within each of the 3 domains of life in a pattern that suggests multiple nonhomologous lateral gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…At each site we calculated the joint posterior probability of two characters a, b (where a, b ∈ { A, C, G, T }) populating the nodes along each branch of the tree: P ( a, b | X ) = P ( a, b ) / P ( X ), using the HKY model (Hasegawa et al, 1985). Full details of this calculation were described previously (Stern et al, 2010). Only sites and branches where P ( a, b | X ) >0.6 were reported.…”
Section: Star Methods Textmentioning
confidence: 99%
“…At each site we calculated the joint posterior probability of two characters a, b (where a, b ∈ { A, C, G, T }) populating the nodes along each branch of the tree: P ( a, b | X ) = P ( a, b ) / P ( X ), using the HKY model (Hasegawa et al, 1985). Full details of this calculation were described previously (Stern et al, 2010). Only sites and branches where P ( a, b | X ) >0.6 were reported.…”
Section: Star Methods Textmentioning
confidence: 99%
“…However, after excluding the outliers (DHFR- 23, 35, 36, 38, and 43), the relationship between activity and growth follows flux dynamics theory that predicts that growth rate is proportional to total folate turnover (see the equation on the right; constants a and b depend on the number of enzymes and topology of the metabolic network) (green line, p-value=10 -4 ). B) Growth rate and activity after the evolution Post-Evolution 38 Ec Theoretical fit: abundance n.d.: (23,35,36,37,38) Growth rate for all theoretical fits in panels (A-D)).…”
Section: Figures and Captionsmentioning
confidence: 99%
“…Additionally, comparative genomics studies have demonstrated that HGT plays an important role in the evolution of the folate metabolic pathway, including the spread of antifolate resistance [22,23]. Moreover, DHFR is an essential enzyme in E. coli with a relatively low basal expression level (approximately 40 copies per cell on average [24]), and its activity is linked to bacterial fitness in a dosage-dependent manner [17].…”
Section: Introductionmentioning
confidence: 99%
“…In extant metabolisms two different thymidylate synthases (ThyA, ThyX) convert 2’-deoxyuridine-5’-monophosphate (dUMP) into 2’-deoxythymidine-5’-monophosphate (dTMP) [ 121 , 122 ] (followed by double phosphorylation). Both enzymes use CH 2 =H 4 folate as CH 3 -source for U → T conversion.…”
Section: The Place Of Rna In the Origin Of Dnamentioning
confidence: 99%